Two Cases of Acute Cholecystitis and Symptomatic Choledocholithiasis in Two Women Less than 40-Years-of-Age with Hormonal Intrauterine Devices - Helen M. Shields; Hasrat Sidhu (Case Reports in Gastrointestinal Medicine)
Levonorgestrel uterine implants are accepted as a safe and efficacious method of contraception. One of the two major health side effects in a large controlled study of subcutaneous hormonal implants with levonorgestrel was a significant increase in gallbladder disease. Gallbladder hypomotility is recognized as a side effect of the levonorgestrel (progesterone). We recently saw on a Gastroenterology Consult Service, two women under 40-years-of-age who had been transferred from outside hospitals with acute cholecystitis with symptomatic choledocholithiasis. Both required Endoscopic Retrograde Cholangiopancreatography and sphincterotomies in addition to laparoscopic cholecystectomies. Both had hormonal (levonorgestrel-releasing) intrauterine devices in place for contraception. Although one patient had a family history of gallstones, the other did not. Both were nonobese, young women patients. We were struck by the coincidence of seeing two such patients. Few articles in the medical literature detail the clinical risks of gallstone disease in patients with hormonal (levonorgestrel-releasing) intrauterine devices. Our experiences with these two patients led us to believe that patients with risk factors for gallstone disease, such as a positive family history, ethnic predisposition, or obesity, should be warned of possible problems, not only with gallbladder disease, but also of common duct stones.